Algeria and its Geo-Political Dimension in American Maneuvers during the Second World War (1940-1942) - Hidougui, Rachid; Sid Ali, Ahmed Messaoud (The Algerian Historical Journal, 2026)
This article reviews Algeria's geostrategic position and its political dimensions during World War II and the Allies' vision of it through the great landing of the Americans and the British on November 8, 1942 in North Africa (Morocco and Algeria), known under the famous code given by F.D.Roosvelt: "Operation Torch». Thus, this landing was the beginning of a major setback for the German power, the operation which was carried out in Casablanca (Morocco), in Oran and west of Algiers, was qualified as "bisector of the war". Indeed, the Allies were able to open another field of war in the south of the Western Front at a time when all of Europe (except Britain) was in Hitler's hands. From this landing, the Allies were able to besiege Rommel's forces and liberate Tunisia, which allowed them to open the way to Sicily, southern Italy and western France.